Developing Web applications - Moseley, Ralph (Wiley, 2007)
Building applications for the Internet is a complex and fast-moving field which utilizes a variety of continually evolving technologies. Whether your perspective is from the client or server side, there are many languages to master - X(HTML), JavaScript, PHP, XML and CSS to name but a few.